Most Effective Leadership Styles for Generation Z: A Review - Kwartawaty, Nana Noviada; Ismail, Mohd Hasmadi; Martadi, Nana Storada Dwi (Formosa Journal of Multidisciplinary Research, 2024)
This review aims to explore the most effective leadership styles for this new generation, taking into account their specific needs, expectations and challenges. The transformational leadership style has proven to be especially beneficial for Generation Z, driving increased enthusiasm, efficiency, and engagement in a variety of organizational environments, including public, corporate, and social settings. The research method used is comparative and uses a mixed research approach. The population is Generation Z from various organizational environments and samples were taken from Generation Z and previous generations. Comparative analysis through statistical tests to compare the effectiveness and preferences of leadership styles between Generation Z and previous generations. Research shows that adopting a transformational leadership approach is the optimal way to lead Generation Z effectively. However, existing research has limitations, highlighting the need for more in-depth research into effective leadership for Generation Z. Future research should focus on several areas, including long-term impacts. Leadership styles on Generation Z's career development and Generation Z's response to the hybrid leadership approach.